THE STRUCTURAL CONSEQUENCES OF CHARGE DISPROPORTIONATION IN MIXED-VALENCE IRON-OXIDES .1. THE CRYSTAL-STRUCTURE OF SR2LAFE3O8.94 AT ROOM-TEMPERATURE AND 50-K - Battle, P; Gibb, T; Lightfoot, P (1990)
The crystal structure of the averaged-valence phase of the rhombohedrally distorted perovskite Sr2La Fe3O8.94 has been refined from neutron powder diffraction data collected at room temperature (space groupR3-c, a = 5.4712Å, α = 60.09°). All iron sites are identical. The crystal and magnetic structures of the low-temperature antiferromagnetic phase showing a charge disproportionation have been similarly obtained at 50 K. The crystal structure has been refined in space groupR3-c, a = 5.4580Å, α = 60.19°; the magnetic structure has been refined inP3-m1 using a model derived from considerations of the exchange interactions between ideal localized electron configurations. The results are interpreted in terms of a charge density wave (CDW) and spin density wave (SDW) propagating along the [111] axis of the crystal and commensurate with the crystal lattice. The apparent absence of a periodic structural distortion (PSD) of the same period as the CDW is surprising, and it is suggested that local variations in the strain field brought about by the disordered arrangement of Sr and La may quench the PSD which would otherwise occur. © 1990 Academic Press, Inc.